Rede virtual de comunicação da informação na perspectiva do regime de informação - (:unkn) unknown (Insitituto Brasileiro de Informação em Ciência e Tecnologia, 2013)
Presents the results of research that uses the concept of 'information system' Gonzalez Gomez to identify elements and actors within the domain of a virtual network of information communication. The research was conducted under the Program Good Agricultural Practices - Beef Cattle at the Brazilian Agricultural Research Corporation - EMBRAPA, which aims to make systems for beef cattle production more profitable and competitive, ensuring the supply of safe food, from of sustainable production systems. From the identification of the elements of 'information system', suggests the formation of a micro to regulate informational content production virtual network formed by the social actors, devices, information and information actions.
Keywords: Política de informação; Regime de informação; Rede virtual de comunicação da informação; Boas Práticas Agropecuárias; Embrapa; Information Policy; Information System; Virtual Network of Information Communication; Good Agricultural Practices; Ciência da informação